Gene Flow Results in High Genetic Similarity between Sibiraea (Rosaceae) Species in the Qinghai-Tibetan Plateau - Fu, Peng-Cheng; Gao, Qing-Bo; Zhang, Fa-Qi; Xing, Rui; Wang, Jiu-Li; Liu, Hai-Rui; Chen, Shi-Long (Frontiers in Plant Science, 2016)
Studying closely related species and divergent populations provides insight into the process of speciation. Previous studies showed that the Sibiraea complex's evolutionary history on the Qinghai-Tibetan Plateau (QTP) was confusing and could not be distinguishable on the molecular level. In this study, the genetic structure and gene flow of S. laevigata and S. angustata on the QTP was examined across 45 populations using 8 microsatellite loci. Microsatellites revealed high genetic diversity in Sibiraea populations. Most of the variance was detected within populations (87.45%) rather than between species (4.39%). We found no significant correlations between genetic and geographical distances among populations. Bayesian cluster analysis grouped all individuals in the sympatric area of Sibiraea into one cluster and other individuals of S. angustata into another. Divergence history analysis based on the approximate Bayesian computation method indicated that the populations of S. angustata at the sympatric area derived from the admixture of 2 species. The assignment test assigned all individuals to populations of their own species rather than its congeneric species. Consistently, intraspecies were detected rather than interspecies ﬁrst-generation migrants. The bidirectional gene flow in long-term patterns between the 2 species was asymmetric, with more from S. angustata to S. laevigata. In conclusion, the Sibiraea complex was distinguishable on the molecular level using microsatellite loci. We found that the high genetic similarity of these 2 species resulted from huge bidirectional gene flow, especially on the sympatric area where population admixtures between the species occurred.